"Concrete" inspired construction of a silicon/carbon hybrid electrode for high performance lithium ion battery. (November 2015) - Yun, Qinbai; Qin, Xianying; Lv, Wei; He, Yan-Bing; Li, Baohua; Kang, Feiyu; Yang, Quan-Hong
Abstract: Graphene and other carbon materials have been combined with various silicon (Si) nanostructures to accommodate the volume change of Si and enhance their electrical conductivity. However, for most of the formed hybrids, their low initial Coulombic efficiency (CE), fragile structures and poor stability cannot meet the practical application of battery. In this work, inspired by the structure and composition of reinforced concrete, a Si nanoparticles embedded in porous carbon/graphene (Si-C/G) electrode is fabricated through directly calcining a Si-polyacrylonitrile/graphene oxide precursor on a current collector. In this concrete-like structure, amorphous carbon, the carbonization product of polyacrylonitrile, acts as the "cement" and binds all components together. The flexible graphene network effectively enhances the strength, flexibility and conductivity of the electrode, as does the reinforcing rod framework in concrete. This carbon/graphene scaffold can accommodate the volume expansion of Si and isolate Si from electrolyte. Such Si-C/G electrode with small surface area and compact structure achieves a high initial CE of 78% and a reversible capacity of 1711 mAh g −1, as well as outstanding rate and cycling performances.